Dial it back [videorecording (DVD)] - Palo, MJ; Keefer, Erin; Baduwalia, Jasmeet; Morrison, Dan; Holdridge, Shannon; Baas, Ashlyn (Filmhub, 2025)
Second-marriage newlyweds are taken aback to learn that their college-aged kids are dating each other. When the family is taken hostage over Christmas, their family dynamics are put to the test.